Impact of Alkali Ions Codoping on Magnetic Properties of La0.9A0.1Mn0.9Co0.1O3 (A: Li, K, Na) Powders and Ceramics - Paweł Głuchowski; Ruslan Nikonkov; Robert Tomala; Wiesław Stręk; Tatsiana Shulha; Maria Serdechnova; Aleksej Zarkov; Tomas Murauskas; Andrius Pakalaniškis; Ramūnas Skaudžius; Aivaras Kareiva; Andrei Kholkin; et al. (Applied Sciences, 2020)
The aim of the work was to check how the introduction of alkali and cobalt ions into a manganese structure can affect the structural disorder and, in consequence, lead to the changes (improvements) of magnetic properties. The high-pressure sintering technique was applied to check if the external factor can modify the magnetization of manganites. Nanocrystalline La0.9A0.1Mn0.9Co0.1O3 (where A is Li, K, Na) powders were synthesized by the combustion technique. The respective powders were used for nanoceramics preparation by the high-pressure sintering technique. The structure and morphology of the compounds were studied by X-ray powder diffraction, scanning electron microscopy and energy-dispersive X-ray spectroscopy. Magnetization studies for all compounds were performed in order to check the changes induced by either codoping or the sintering pressure. It was found that the type of the dopant ion and sintering pressure produced significant changes to the magnetic properties of the studied compounds. Alkali ions lead to the stabilization of Co ions in the +2 oxidation state and the formation of positive exchange interactions Mn3+–Mn4+ and Co2+–Mn4+ and the subsequent increase in remanent magnetization. High sintering pressure leads to a decrease in grain size and reduction of long-range ferromagnetic order and lower magnetization.